Long non-coding HOXA-AS3 contributes to osteosarcoma progression through the miR-1286/TEAD1 axis - Xiao, Xiangjun; Liu, Mingjiang; Xie, Songlin; Liu, Changxiong; Huang, Xinfeng; Huang, Xiongjie (Journal of orthopaedic surgery and research, 2023)
Long non-coding RNA (lncRNA) HOXA cluster antisense RNA 3 (HOXA-AS3) regulates the progression of several types of human malignancy. However, the role and potential mechanism of HOXA-AS3 in osteosarcoma (OS) remain unknown. In this study, upregulation of HOXA-AS3 was observed in OS tissues and cell lines and associated with poor clinical outcomes. Silencing of HOXA-AS3 significantly inhibited the proliferation, migration and invasion of OS cells in vitro and suppressed the tumorigenesis of OS cells in vivo. Furthermore, knockdown of HOXA-AS3 inhibited the proliferation and migration of human umbilical vein endothelial cells (HUVECs) and epithelial-to-mesenchymal transition (EMT) in OS. Further investigation of this mechanism revealed that HOXA-AS3 could directly upregulate the expression of TEAD1 via its competing endogenous RNA (ceRNA) activity on miR-1286. This study clarified the oncogenic roles of the HOXA-AS3/miR-1286/TEAD1 axis in OS progression, suggesting a novel therapeutic target for OS.